Hukuman Tambahan Berupa Pembayaran Ganti Rugi bagi Pelaku Tindak Pidana Korupsi dalam Undang-Undang Tipikor Perspektif Hukum Pidana Islam - Riva Luviana (Rechtenstudent, 2020)
Corruption is a crime that can be categorized as an extraordinary crime because it has damaged not only state finances and the country's economic potential, but has also destroyed the socio-cultural pillars, political morals and the legal system of national security. The focus of the problems examined in these theses are 1) How to implement additional penalties for perpetrators of criminal acts of corruption in the form of compensation payments in article 18 paragraph (1) Letter b Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning eradication corruption. 2) How does Islamic criminal law review the implementation of additional penalties for perpetrators of criminal acts of corruption in the form of replacement money in article 18 paragraph (1) letter b of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the eradication of corruption? Based on Islamic criminal law, compensation in the form of payment is included in the category of additional punishment ('Uqubah Taba'iyah) which follows the basic sentence without requiring a separate decision. Compensation penalties are also included in the category of ta'zir punishment in the form of assets.